Epidemiological characteristics of hemophilia in the pre-primary prophylaxis era: a historical cohort - Catelli, Dayenne Helena; Portich, Júlia Plentz; Luz, Adriana Celia; Diaz, Giovana Fecker da Costa; de Ourique, Liliane Ourique; Hoffmann, Daniel Sander; Bosi, Guilherme Rasia; Spessato, Barbara Coiro; Sekine, Leo; Silla, Lucia Mariano da Rocha (Clinical and Biomedical Research, 2021)
Introduction: Epidemiological studies on hemophilia in the Brazilian population are historically scarce. Despite the continuous effort made by the National Program of Inherited Bleeding Disorders to map this condition, little information is available, especially on the period prior to program conception. Therefore, the present study aims to assess the epidemiological, serological, and clinical characteristics of patients with hemophilia in the state of Rio Grande do Sul, Brazil. Methods: A total of 455 patients had their medical records reviewed from January 1, 2003 to December 31, 2007. Results: We observed a remarkable prevalence of hepatitis C virus (HCV) infection in patients with both hemophilia A and B, and this prevalence significantly increased along with age (p < 0.001). No positive anti-HCV results were observed among children younger than 5 years old. There was a significant correlation between the severity of hemophilia and the number of arthropathies in all age categories. Considering the presence of inhibitors, a significant difference was observed between age groups, as older patients had higher inhibitor titers. There was a significant correlation between mean coagulation factor consumption and the number of arthropathies in patients over 5 years old. Conclusions: This profile analysis of patients with hemophilia reflects a gradual improvement in treatment safety and efficiency, as well as the need for continued investment in this population.